Meta-analysis of Therapeutic Effect of Warm Acupuncture and Moxibustion on Knee Osteoarthritis of Yang Deficiency and Cold Coagulation and Research on Regularity of Acupoint Selection - Zeling HUANG; Shanni SHI; Junjun HE; Hongjian GAO; Haiya GE; Zhenqiang HONG (康复学报)
Objective:To evaluate the efficacy of warm acupuncture and moxibustion in the treatment of knee osteoarthritis(KOA)of Yang deficiency and cold coagulation, and analyze the regularity of acupoint selection.Methods:Data were searched from the databases of PubMed, Cochrane Library, CNKI, VIP and Wanfang Data. The randomized controlled trials(RCTs)of warming acupuncture and moxibustion and other therapies in the treatment of KOA of Yang deficiency and cold coagulation were included. The retrieval time for each database was from the establishment of the database to February 1, 2020.Outcome indicators included visual analogue scale(VAS), WOMAC osteoarthritis index, symptom and sign score, total effective rate. Two researchers independently screened the literature, extracted the data and evaluated the quality of the included studies, quality was assessed according to the bias risk assessment tool recommended by the Cochrane Manual. RevMan 5.3 software was used for data analysis, continuous variables were represented by mean difference(MD)and 95%CI while dichotomous variables were represented by risk ratio(OR)and 95%CI.If the heterogeneity in included studies was little(I2<50%), a fixed effect model would be used. In contrast, if I2≥50%, a random effect model would be used. Excel software was used to analyze the acupoint selection prescriptions of warm acupuncture and moxibustion, and to explore the acupoint selection regularity of warm acupuncture and moxibustion in the treatment of KOA of Yang deficiency and cold coagulation.Results:A total of 18 RCTs and 1 209 patients were included. Meta analysis results showed that: compared with the control group, VAS score in the warming acupuncture and moxibustion group after treatment[MD=-0.93, 95%CI(-1.20, -0.67), P<0.000 01], WOMAC osteoarthritis index[MD=-8.91, 95%CI(-12.58, -5.23), P<0.000 01], symptoms and signs scores[MD=-2.39, 95%CI(-3.79, -0.99), P=0.000 8]was significantly lower, while total effective rate was significantly higher[OR=3.41, 95%CI(2.27, 5.13), P<0.000 01].In the 18 prescriptions, 22 acupoints were involved, and the total use frequency of acupoints was 103 times, there were more acupoints with Dubi(ST35), Neixiyan(EX-LE4), Yanglingquan(GB34), Zusanli(ST36), Liangqiu(ST34), Xuehai(SP10), Heding(EX-LE2), Ashi point, Guanyuan(RN4), and Xiyangguan(GB33). The selected points of warm acupuncture and moxibustion treatment mainly concentrated on the stomach meridian of Foot-Yangming, the extraordinary points, the gallbladder meridian of Foot-Shaoyang, the spleen meridian of Foot-Taiyin and Ren meridian.Conclusion:Warming acupuncture and moxibustion can effectively improve the symptoms of joint pain, morning stiffness, dysfunction and limb chills in KOA patients of Yang deficiency and cold coagulation, the clinical effective rate is good. However, the further research needs to carry out a multi-center, large-sample, high-quality randomized controlled clinical study to provide more reliable evidence for warm acupuncture and moxibustion in the treatment of KOA of Yang deficiency and cold coagulation.